2003
DOI: 10.1016/s0376-6357(03)00022-6
|View full text |Cite
|
Sign up to set email alerts
|

Successive two-item same-different discrimination and concept learning by pigeons

Abstract: Four pigeons were trained in a successive same/different procedure involving the alternation of two stimuli per trial. Using a go/no-go procedure, two different or two identical color photographs were alternated, with a brief, dark, inter-stimulus interval, on a computer screen for 20 s. Pigeons learned to discriminate between same (S+) and different (D−) sequences with moderate to large contrasts between successive pictures. Analyses of pecking behavior within single trials revealed this discrimination emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 31 publications
5
58
0
Order By: Relevance
“…In addition to learning a single, broadly applied rule, we have consistently found that pigeons can transfer this solution to novel exemplars from both within (Cook et al, 1995; and outside (Cook et al, 1999) the range of stimuli experienced during training. Recently, we found that they can also learn and transfer this behavior when trained and tested with successively presented photographic and video stimuli (Cook et al, 2003). As a whole, these results seem most consistent with the hypothesis that pigeons can detect, recognize, and abstract S/D visual relations in a variety of different test procedures.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…In addition to learning a single, broadly applied rule, we have consistently found that pigeons can transfer this solution to novel exemplars from both within (Cook et al, 1995; and outside (Cook et al, 1999) the range of stimuli experienced during training. Recently, we found that they can also learn and transfer this behavior when trained and tested with successively presented photographic and video stimuli (Cook et al, 2003). As a whole, these results seem most consistent with the hypothesis that pigeons can detect, recognize, and abstract S/D visual relations in a variety of different test procedures.…”
supporting
confidence: 82%
“…This suggests that their problem may have been more attentional than conceptual in nature. Interestingly, in Cook et al's (2003) tests with a successive two-item procedure, the pigeons showed more difficulty in learning and transferring S/D discriminations with grayscale pictures than with fully colored versions of the same pictures. As such, shape differences not only may be perceptually more difficult for pigeons to detect, but also may be harder to conceptualize.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the visual domain, birds have been shown to have the propensity of being controlled by both absolute and relational factors (Cook, Kelly, & Katz, 2003;Cook, Levison, Gillett, & Blaisdell, 2005;Wasserman, Frank, & Young, 2002). The same appears true for the auditory modality.…”
Section: Discussionmentioning
confidence: 89%
“…The pigeons consistently needed several auditory presentations, approximately 3 to 5, to consistently exhibit stimulus control within a sequence. We have previously found using successive visual presentations of color pictures clear evidence that S/D discrimination emerged after only the minimal number of two presentations (Cook, Kelly, & Katz, 2003). Another difference between the modalities was that we needed an asymmetrical learning procedure for the auditory stimuli that we have not had to employ in our visual studies.…”
Section: Discussionmentioning
confidence: 99%